(untitled) (Journal of NELTA, 2018)
Communicative Language Teaching (CLT) is a learner-centered approach for language teaching and learning. In the CLT context, learner’s role changes from that of a passive receiver to an active participant engaging in diverse classroom activities that promote communicative competence. Again, L2 learners are supposed to learn the language by using it for different tasks, and taking part in pair work, group work, role play, and discussion inside classrooms. This study aims to find out gaps, if any, between learner roles as advocated in CLT theory and as practiced by learners in the higher secondary classrooms in Bangladesh while teaching/learning English following this approach, and its relation to poor ‘learning outcomes’. Journal of NELTA, Vol 20 No. 1-2, December 2015, page: 34-40